An Evaluation of the Development Trajectory of the Construction Sector in the Context of Global Crises Using Hellwig’s Synthetic Development Measure - The Case of Poland - Joanna CYMERMAN (Communications of International Proceedings, 2025)
The principal aim of the study was to assess the development of the construction sector within the broader context of global crises, using Hellwig’s synthetic development measure, with Poland serving as the case study. The temporal scope of the analysis covered the past 18 years (2007–2024), a period marked by a high incidence of global shocks, including the global financial crisis of 2008, the Eurozone sovereign debt crisis of 2011, the COVID‑19 pandemic, and the onset of Russia’s full‑scale war against Ukraine in 2022. For the construction of Hellwig’s synthetic development measure, nine diagnostic variables were selected. The values obtained from Hellwig’s synthetic development measure for the construction sector clearly indicated a dynamic expansion of this sector in Poland over the period under analysis. Additionally, cyclical fluctuations in the value of the measure were observed, confirming the presence of cyclical variability within the construction sector.
Keywords: construction sector; global crisis; Hellwig’s synthetic development measure.